Nearpod Application-Based Diagnostic E-Assessment Interest in Learning Mathematics for Grade 4 Elementary School Students - Wahyuningtyas, Dyah Tri; Risma Meilia Berliana; Nyamik Rahayu Sesanti (Jurnal Pendidikan Indonesia, 2024)
Diagnostic assessments in elementary schools still use paper media and teachers rarely use technology in making or applying assessments in the classroom. The role of the teacher is as the main source of students in learning in class, so teachers must create creative learning, especially by using technology. The type of research used is development research which aims to develop a product electronic assessment diagnostics to increase elementary school students' interest in learning mathematics and measure feasibility, practicality and effectiveness electronic assessment which has been developed. The population in this study was one institution in an area, while the research sample for the small-scale trial was 5 children and the large-scale trial was 21 children. Samples were taken in 4th grade of elementary school. Data collection in this research used expert validation, questionnaires and checklist questionnaires. Researchers tested the validity of the data by using expert validity tests and student and teacher response questionnaires. N-Gain Results initial test And post test with a mean of 0.75. Based on these results, it can be seen that by utilizing technology it is possible to increase students' interest in learning, this can be seen from the significant increase in student learning outcomes. Apart from that, students can also learn while playing by utilizing existing technology. The implications of this research can encourage teachers to adopt more interactive and data-based learning technology, where the Nearpod application allows teachers to provide real-time feedback and monitor individual student learning difficulties.